2021
DOI: 10.33448/rsd-v10i12.20307
|View full text |Cite
|
Sign up to set email alerts
|

The use of Annona squamosa seed, leaf and bark as an alternative in the control of Cryptotermes brevis

Abstract: The changes in human behavior towards the environment, the disorderly urban development, globalization and climate change are some of the factors that promote the occurrence and spread of pests that somehow bring damage. This occurrence is aimed at termites, which are insects known for their habit of feeding on cellulose, that is, papers, books, and wooden structures, causing accidents. Cryptotermes brevis are a major cause of damage to various wood species commonly used throughout the country, which cause maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Sini et al [15] reported that the A. squamosa L. extract, which contains octadecenoic acid (oleic acid), showed insecticidal activity against the insects. The toxicity of A. squamosa L. leaf, bark, and seed extract against Cryptotermes brevis was reported by Alves et al [16] among the leaf, bark, and seed extracts, he reported that seed extract is more effective for the wood-destroying termites Cryptotermes brevis.…”
Section: Toxicity Of Petroleum Ether Extract Of a Squamosa Seedsmentioning
confidence: 82%
See 1 more Smart Citation
“…Sini et al [15] reported that the A. squamosa L. extract, which contains octadecenoic acid (oleic acid), showed insecticidal activity against the insects. The toxicity of A. squamosa L. leaf, bark, and seed extract against Cryptotermes brevis was reported by Alves et al [16] among the leaf, bark, and seed extracts, he reported that seed extract is more effective for the wood-destroying termites Cryptotermes brevis.…”
Section: Toxicity Of Petroleum Ether Extract Of a Squamosa Seedsmentioning
confidence: 82%
“…Routine inspections by pest control experts are vital for early detection and mitigation. Plant extracts are potential sources of botanical insecticides to control various arthropod pests, and their use for pest management has been recorded as an alternative to synthetic chemical insecticides [4,5]. Synthetic chemicals like fipronil, and imidacloprid can be used for the management of termites but they pose a threat to the environment.…”
Section: Introductionmentioning
confidence: 99%